Kérygma víry církve ve vztahu k současnému českému ateismu - Paclík, Miloslav (Kerygmat wiary Kościoła wobec współczesnego ateizmu czeskiego, 2018)
The central problem of this disertation discourse is going to be the analysis of the problem of Czech atheism. I try to analyse the concept of atheism in the view of current theology, which means focus on this topic in the Holy Bible, analysis of the concept of atheism in relationship to Magisterium of the Church in order to find a closer look at causes of atheism in Bohemia and specify and define ways to dealing with the problem.
Rozprawa obroniona w 2019 roku.
Keywords: kerygmat; Ateizm; Kościół katolicki; Czechy